2017
DOI: 10.1037/pas0000387
|View full text |Cite
|
Sign up to set email alerts
|

Measuring adult picky eating: The development of a multidimensional self-report instrument.

Abstract: A brief multidimensional measure of adult picky eating (PE) behavior was developed using a large U.S. adult sample. In addition, the study explored associations between specific aspects of adult PE behavior and psychosocial impairment in effort to support the inclusion of adults in the Diagnostic and Statistical Manual for Mental Disorders-Fifth Edition (DSM-5) avoidant-restrictive food intake disorder (ARFID). The study included 3 phases of qualitative and quantitative data collection. Participants were 1,663… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(115 citation statements)
references
References 47 publications
12
83
1
19
Order By: Relevance
“…However, compared to patients with other eating disorders, ARFID patients have been reported to score significantly lower on the Children's Eating Attitudes Test (Nicely et al, ; Ornstein et al, ) and on all subscales of the Eating Attitudes Test and the Eating Disorder Inventory (Nakai et al, ). Notably, a couple of these studies (Ellis, Galloway, Webb, & Martz, ; Zickgraf & Ellis, ) utilize the highly opaque convenience samples of Amazon's Mechanical Turk web panel, the validity of which has, as seen above, been questioned (Landers & Behrend, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to patients with other eating disorders, ARFID patients have been reported to score significantly lower on the Children's Eating Attitudes Test (Nicely et al, ; Ornstein et al, ) and on all subscales of the Eating Attitudes Test and the Eating Disorder Inventory (Nakai et al, ). Notably, a couple of these studies (Ellis, Galloway, Webb, & Martz, ; Zickgraf & Ellis, ) utilize the highly opaque convenience samples of Amazon's Mechanical Turk web panel, the validity of which has, as seen above, been questioned (Landers & Behrend, ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a couple of these studies (Ellis, Galloway, Webb, & Martz, 2017; utilize the highly opaque convenience samples of Amazon's Mechanical Turk web panel, the validity of which has, as seen above, been questioned (Landers & Behrend, 2015).…”
Section: Feighner Criterion 2: Laboratory Findings Psychological Tmentioning
confidence: 99%
“…Some of the items comprising the busy daily life and preferences scale, in particular taste and routine/what I’m used to eating, may be tapping into a related construct known as picky eating. Picky eating has been assessed in other studies with the Adult Picky Eating Questionnaire (APEQ) [ 31 ]. Similar to our findings with busy daily life and preferences FCP, picky eating has also been associated with lower amounts and variety of FV intake among college students [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In toddlers, preschoolers, and school‐aged children, a recent review reported that nearly equivalent numbers of studies found small negative correlations and no relationship between PE and growth (Brown, Vander Schaaf, Cohen, Irby, & Skelton, ). In most published adult samples to date, there has been a null relationship between PE and BMI (e.g., Ellis, Galloway, et al, ; Ellis, Galloway, Webb, & Martz, ; Wildes et al, ; Zickgraf et al, ; Zickgraf & Ellis, ; Zickgraf & Schepps, ). While there may be a relationship between PE and psychosocial impairment (Ellis, Galloway, et al, ; Wildes et al, ), this association has been found to be attenuated after controlling for restrictive eating due to fear and low appetite (Zickgraf & Ellis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the CIA was originally designed to capture impairment related to anorexia and bulimia nervosa, it includes items measuring impairment related to the physiological effects of starvation, as well as items measuring personal impairment and social impairment (e.g., Zickgraf & Ellis, ). Picky eating appears to be most strongly related to eating‐related social anxiety and social impairment (e.g., Ellis, Galloway, et al, ), and the psychosocial impacts of PE may best be captured by the Personal and Social subscales of the CIA. As PE can be associated with increased, decreased, or appropriate caloric intake (Zickgraf, Murray, et al, ), a substantial proportion of individuals with PE are unlikely to experience impairment related to starvation.…”
Section: Introductionmentioning
confidence: 99%